Students’ conceptual understanding in learning mathematics through scientific approach with mind mapping - Dewi Agus Tiani; Rahmah Johar; Bahrun Bahrun (Universitas Islam Negeri (UIN) Mataram, 2019)
[English]: Students' ability to understand mathematics concepts remains problematic even though conceptual understanding is critical in learning mathematics. Indeed, one of the efforts to develop conceptual understanding by actively engaging students in mathematics learning is to apply the scientific approach with mind mapping. This study aimed to investigate the development of secondary students' conceptual understanding through the use of the scientific approach with mind mapping in the number sequences topic. The present study employed a qualitative descriptive approach which involves 24 ninth-grade students. Two students (S-1 and S-2) who respectively represent low and mid-achieving groups of mathematics ability were selected as the subjects for the focus of the investigation. They were purposively selected based on the results of preliminary test and teacher consultation. Data were collected by administering a conceptual understanding test and semi-structured clinical interview. The results of the test and transcript of the interview were analyzed based on the indicators of conceptual understanding to investigate the students' development of number sequences concepts. The results showed that S-1 fulfilled the indicators of conceptual understanding in all lessons, while S-2 only met one indicator in the third lesson. However, the post-test revealed that the students show significant progress in conceptually understanding the number sequence. The present study concludes that applying scientific approach with mind mapping support students’ development of conceptual understanding. Keywords: Conceptual understanding, Scientific approach, Mind mapping, Number sequences [Bahasa]: Kemampuan siswa dalam memahami konsep matematika masih bermasalah padahal pemahaman konsep merupakan bagian paling penting dalam pembelajaran matematika. Dalam hal ini, salah satu upaya untuk mengembangkan pemahaman konsep dengan melibatkan siswa secara aktif dalam pembelajaran yaitu menerapkan pendekatan saintifik berbantuan mind mapping. Penelitian ini bertujuan untuk mengalisis perkembangan pemahaman konsep siswa SMP melalui pendekatan saintifik berbantuan mind mapping pada materi barisan bilangan. Penelitian ini menerapkan pendekatan kualitatif deskriptif yang melibatkan 24 siswa kelas IX. Dua siswa (S-1 dan S-2) yang masing-masing mewakili kemampuan rendah dan sedang dalam matematika dari 24 siswa tersebut dijadikan sebagai fokus investigasi. Kedua siswa tersebut dipilih berdasarkan hasil tes awal dan konsultasi dengan guru. Pengumpulan data dilakukan melalui pemberian tes pemahaman konsep dan wawancara semi-terstruktur. Hasil tes dan transkrip wawancara dianalisis berdasarkan indikator pemahaman konsep untuk menganalisis perkembangan pemahaman konsep barisan bilangan. Hasil penelitian menunjukkan bahwa S-1 memenuhi indikator pemahaman konsep untuk semua pertemuan, sedangkan S-2 hanya memenuhi indikator pada pertemuan ketiga. Namun, hasil post-tes menunjukkan capaian pemahaman konsep yang lebih baik dari kedua siswa. Penelitian ini menunjukkan bahwa penerapan pendekatan saintifik dengan mind mapping dalam pembelajaran matematika mendukung pengembangan pemahaman konsep siswa. Kata kunci: Pemahaman konsep, Pendekatan saintifik, Mind mapping, Barisan bilangan